Performance analysis of a VDFLL GNSS receiver architecture under ionospheric scintillation and multipath conditions - Sousa, Fernando (2015)
A noncoherent vector delay/frequency-locked loop (VDFLL) architecture for GNSS receivers is proposed. A bank of code and frequency discriminators feeds a central extended Kalman filter that estimates the receiver's position and velocity, besides the clock error. The VDFLL architecture performance is compared with the one of the classic scalar receiver, both for scintillation and multipath scenarios, in terms of position errors. We show that the proposed solution is superior to the conventional scalar receivers, which tend to lose lock rapidly, due to the sudden drops of the received signal power.